Comparison of the Efficacy and Safety of Intravitreal Conbercept with Intravitreal Ranibizumab for Treatment of Diabetic Macular Edema: A Meta-Analysis - Xiaolei Sun; Jingjing Zhang; Jingyi Tian; Shijiu Chen; Fanxing Zeng; Gongqiang Yuan (Journal of Ophthalmology)
Introduction. This meta-analysis aimed to compare the therapeutic effect and safety of intravitreal conbercept (IVC) versus intravitreal ranibizumab (IVR) in treatment of diabetic macular edema (DME). Methods. Relevant studies were identified through systemic searches of PubMed, Embase, Cochrane Library, Ovid, CNKI, and Wanfang database up to 28 February 2019. Changes in central retinal thickness (CRT) in μm and best-corrected visual acuity (BCVA) in logMAR equivalents at 1, 3, and 6 months after initial treatment were performed by pooled analysis. Adverse events (AEs) were evaluated. Results. Eight articles involving 588 patients with DME were identified for this meta-analysis. The results showed that IVC significantly improved BCVA compared with IVR at 6 mo (SMD = −0.74 95% CI: −1.28 to −0.2; p=0.029) in patients with DME. IVC was superior to IVR in reducing central retinal thickness (CRT at 1 mo (p<0.0001), 3 mo (p=0.025), and 6 mo (p=0.019)) from baseline with statistical significance. For AEs, the pooled results showed that no significant difference in the risk of intraocular pressure increased (OR = 1.71; 95% CI: 0.55 to 5.25; p=0.352) or conjunctival hemorrhage (OR = 0.89; 95% CI: 0.34 to 2.34; p=0.65) between two groups. Conclusions. This meta-analysis showed that IVC trended to be more effective than IVR in terms of functional and anatomic outcomes for treating DME.